Idols of Modernity : Movie Stars of the 1920s - Petro, Patrice, 1957- (Book collections on Project MUSE., 2010)
With its sharp focus on stardom during the 1920s, Idols of Modernity reveals strong connections and dissonances in matters of storytelling and performance that can be traced both backward and forward, across Europe, Asia, and the United States, from the silent era into the emergence of sound. Bringing together the best new work on cinema and stardom in the 1920s, this illustrated collection showcases the range of complex social, institutional, and aesthetic issues at work in American cinema of this time.